Appendage pigmentation and temperature acclimation correlate with survival during acute heat stress in the upside-down jellyfish, Cassiopea xamachana - Maloney, Megan E.; Buckley, Katherine M.; Strader, Marie E. (Frontiers in Ecology and Evolution, 2024)
IntroductionUpside-down jellyfish (Cassiopea sp.) are highly tolerant to multiple abiotic stressors, including fluctuating temperatures associated with shallow marine habitats. This resilience may underlie the ability of Cassiopea sp. to inhabit a wide variety of tropical habitats across the globe. Additionally, Cassiopea sp. are marked by a conspicuous array of appendage coloration; individual medusae vary in the hue and number of oral appendages, which are often strikingly blue. The function of this coloration is not understood. We aimed to understand how extrinsic (temperature, location) and intrinsic (host color) factors may shape thermal tolerance.MethodsAdult Cassiopea xamachana were collected from two sites that vary in daily temperature range within the Florida Keys and were subjected to acute lethal heat stress. To quantify a whole-organism response to heat, we measured changes in bell pulsation, which likely plays a role in feeding, oxygen exchange, and symbiont uptake. Finally, color morphs were acclimated at either ambient (26°C) or elevated (33°C) temperatures.ResultsC. xamachana from two locations that vary in thermal range do not exhibit different responses to heat, suggesting that temperature fluctuations do not prime individuals for higher thermal tolerance. Additionally, C. xamachana with blue appendages survived significantly higher temperatures and exhibited less change in bell pulsation rates compared to non-blue individuals. We found that acclimation at 33°C, as well as appendage color in each treatment, led to higher survival under acute heat stress.DiscussionThese findings highlight the importance of temperature and coloration in Cassiopea xamachana resilience during heat stress.